Mongameli Mabona His Life and Work - Wolff, Ernst (Leuven University Press, 2020)
The life and work of a remarkably versatile and pioneering South African thinkerMongameli Anthony Mabona (1929) is a singular South African scholar with an exceptional life path. Yet, he is a wrongly forgotten figure today. British imperialism and apartheid shaped the world into which he was born and, to a large extent, these powers carved out his destiny for him. Nevertheless, a curious set of coincidences enabled him to obtain a tertiary education as a priest, to pursue his doctoral studies in Italy and to befriend Alioune Diop. He is one of the first published philosophers of Anglophone Africa and holds doctorates in theology and anthropology. His opposition to institutionalized racism - an opposition which included his co-authoring the 1970 "Black Priests' Manifesto" - eventually led to his exile. This book is the first study of any kind devoted to Mabona. It documents his life and offers a synoptic reading of his scholarly and poetic work.